4 - Comparing Pedagogy in Kenya’s Public Universities: The Roles of University Managers - Kilonzo, Susan M.; Onkware, Kennedy; Oloo, Pamela A.; Omare, Simon G. (Journal of Higher Education in Africa, 2022)
Past studies have shown that the increased enrolment of students in public universities has not been matched with supporting human and technical resources. This has affected the quality of teaching and learning. This article examines pedagogical approaches in the context of mass expansion of tertiary education in selected public universities in Kenya. Further, the authors explore how managers within these institutions support academic staff in pedagogical innovations. The results from a survey of selected public universities showed that certain teaching and learning pedagogies have been favoured and used in these institutions to accommodate the increasing number of students. Further, although the study shows that there is an effort on the side of university lecturers and managers to use and/or support pedagogies that favour the large number of students, there are bottlenecks that are currently beyond their control. These include inadequate funding, staffing, and physical facilities, among others. Subsequently, there are calls for the Ministry of Education and Commission for University Education to work hand in hand with universities if significant quality education is to be realised in Kenya’s public universities.